Social Issues in Sustainable Fisheries Management - Urquhart, Julie; Acott, Tim G.; Symes, David; Zhao, Minghua; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
This volume is an interdisciplinary mix of perspectives and studies on social issues in fisheries from a diverse range of case studies and research disciplines. The case is made regarding the dearth of attention to socio-cultural considerations which to date have been largely treated as an externality of fisheries policy. It will be valuable to researchers and decision makers interested in understanding the social dimension of fisheries and provides a timely and relevant compilation of research and analysis on some of the critical socio-cultural issues facing fisheries management and fishing communities today.
Part I. Issues in Governance and Co-management -- Part II. Issues in Local Ecological Knowledge and Scientific Evidence -- Part III. Issues in Sustaining Fisher Livelihoods -- Part IV. Issues in Gender Roles -- Part V. Issues in Social Identity and Cultural Heritage.
Keywords: Environmental sciences; Wildlife management; Sustainable development; Human Geography; Environment; Sustainable Development; Human Geography; Fish & Wildlife Biology & Management